Enhancement of mechanical properties of poly(vinyl chloride) with polymethyl methacrylate-grafted halloysite nanotube (eXPRESS Polymer Letters, 2011)
Halloysite nanotubes(HNTs) grafted with Polymethyl methacrylate(PMMA) were synthesized via radical polymerization. The properties of PMMA-grafted HNTs were characterized by transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and X-ray photoelectron spectroscopy (XPS). The results showed that PMMA grafted to the surfaces of HNTs successfully. Then, PVC/PMMA-grafted HNTs nanocomposites were prepared by melt compounding. The morphology, mechanical properties and thermal properties of the nanocomposites were investigated. PMMA-grafted HNTs can effectively improve the toughness, strength and modulus of PVC. The glass transition and thermal decomposition temperatures of PVC phase in PVC/PMMA-grafted HNTs nanocomposites are shifted toward slightly higher temperatures. The grafted HNTs were uniformly dispersed in PVC matrix as revealed by TEM photos. The fracture surfaces of the nanocomposites exhibited plastic deformation feature indicating ductile fracture behaviors. The improvement of toughness of PVC by PMMA-grafted HNTs was attributed to the improved interfacial bonding by grafting and the toughening mechanism was explained according to the cavitation mechanism.